MENINGKATKAN KEMAMPUAN MENGENAL WARNA MELALUI PERMAINAN MENGELOMPOKKAN BOLA WARNA PADA ANAK USIA 4 – 5 TAHUN: Mengembangkan kemampuan mengenal warna - azizah, latifah nur; Permata, Rista Dwi (Jurnal Teladan: Jurnal Ilmu Pendidikan dan Pembelajaran, 2020)
Abstract Research is based on the problem in Kindergarten A ages 4-5 years who lags behind knowing color. Introducing colors using color balls is the aim of this study. The classroom action research method chosen for the following research, observation and interviews are data collection techniques that researchers use. The subjects of this research are 26 children of Dharma Wanita Siding Village. Research shows an increase in the ability to recognize color in children, this can be seen from the percentage of pre-cycle results, cycle I, to cycle II. In pre-cycle children with 1 star have a percentage of 15%, children with 2 stars are 12% and 73% for children with 3 stars. In the first cycle, children with 1 star decreased to 8%, 2 stars are still equal to 12% and 3 stars increased by 80%. In the second cycle, children with 1 star experience decreased again by 0%, 2 star children as much as 15% and 3 star children as much as 85%. The conclusion of this study is the game of grouping colors with a good color ball media to improve the ability to recognize color in children aged 4 - 5 years in Dharma Wanita Kindergarten, Siding Village. Keywords : Cognitive, Getting to know the color, Color Ball.